Does gender modify associations between self rated health and the social and economic characteristics of local environments?. Issue 6 (12th May 2006) - Kavanagh, Anne M; Bentley, Rebecca; Turrell, Gavin; Broom, Dorothy H; Subramanian, S V
Abstract : Objectives: To examine whether area level socioeconomic disadvantage and social capital have different relations with women's and men's self rated health. Methods: The study used data from 15 112 respondents to the 1998 Tasmanian (Australia) healthy communities study (60% response rate) nested within 41 statistical local areas. Gender stratified analyses were conducted of the associations between the index of relative socioeconomic disadvantage (IRSD) and social capital (neighbourhood integration, neighbourhood alienation, neighbourhood safety, political participation, social trust, trust in institutions) and individual level self rated health using multilevel logistic regression analysis before (age only) and after adjustment for individual level confounders (marital status, indigenous status, income, education, occupation, smoking). The study also tested for interactions between gender and area level variables. Results: IRSD was associated with poor self rated health for women (age adjusted p<0.001) and men (age adjusted p<0.001), however, the estimates attenuated when adjusted for individual level variables. Political participation and neighbourhood safety were protective for women's self rated health but not for men's. Interactions between gender and political participation (p = 0.010) and neighbourhood safety (p = 0.023) were significant. Conclusions: These finding suggest that women may benefit more than men from higher levels of area social capital.